PERAN PEMUDA DALAM PENDIDKAN PERILAKU RELIGIUS MASYARAKAT ISLAM DI PEDESAAN PONOROGO - Siti Amiroh; Katniy, Katni; Yudha Mahendra; Erdian Hidayat (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This study discusses the role of the Youth of Karang Taruna GTC in Krajan Hamlet, Baosan Lor Village, Ponorogo in shaping the religious behavior of the community through religious activities. The results of the study indicate that the Youth of Karang Taruna GTC has played a significant role in increasing the religious awareness of the community, creating a harmonious environment, and developing leadership and social responsibility for youth. The main supporting factors are the active role of administrators and members, as well as community support, while the inhibiting factor is the lack of active role of some members. This study concludes that the Youth of Karang Taruna GTC can be an example for other youth in shaping the religious behavior of the community Youth have played a crucial role in the history of Islamic progress, both as agents of change and as pioneers in various fields. They have demonstrated a high level of enthusiasm and dedication in studying and spreading Islamic teachings, as well as in fighting for freedom and justice. Muslim youth have become exemplary in developing Islamic science, art, and culture, as well as in building a civilized and morally upright society. The research approach is qualitative, a type of field research. The researcher serves as the key instrument, conducting interviews, observations, and documentation. Data analysis involves reduction, display, and verification, and data validity is validated through triangulation.